Assessment of the susceptibility of the coast of Astypalaea Island (S.E. Aegean Sea) to sea level rise. - Papoulia, M.; Karymbalis, E.; Gaki-Papanastassiou, K.; Maroukian, H. (Bulletin of the Geological Society of Greece, 2013)
The aim of this paper is the classification of the coast of Astypalaea Island (S.E Aegean Sea) according to its susceptibility to an anticipated future sea-level rise, using the Coastal Sensitivity Index (CSI), and utilizing GIS technology. This index allows the following six physical variables: geomorphology, coastal slope, relative sea-level rise rate, shoreline erosion or accretion rate, mean tidal range and mean wave height, to be related in a semi-quantitative manner. Each variable is ranked on the basis of its potential contribution to physical changes on the coast as sea-level rises. Following the CSI calculation, a map is produced for the coastline of the island. This map showed that an extensive length of the coast (121.5 km, corresponding to 84.6% of the island’s coastline) is characterized as very low and low sensitive. Only 12.1 km of the coast, corresponding to 8.5% of the entire coastline, is characterized as very highly and highly sensitive to sea- level rise, primarily due to the low topography and the presence of highly erodible geological formations and landforms. Areas of high and very high CSI values host socioeconomically important land uses and activities as well as environmentally protected areas.